PENYELESAIAN SENGKETA TRANSAKSI ELEKTRONIK - Gunawan Widjaja; Anastasia Prestika; Olivia Pauline Hartanti; Achmad Fazrin (Cross-border, 2018)
In Electronic Transactions dispute resolution can be carried out through the courts (Class action and Civil Lawsuits) or non-litigation settlements (Mediation, Negotiation, and Arbitration).